MF-RALU: design of an efficient multi-functional reversible arithmetic and logic unit for processor design on field programmable gate array platform - Girija Sanjeevaiah; Sangeetha Bhandari Gajanan (International Journal of Electrical and Computer Engineering (IJECE), 2023)
Most modern computer applications use reversible logic gates to solve power dissipation issues. This manuscript uses an efficient multi-functional reversible arithmetic and logical unit (MF-RALU) to perform 30 operations. The 32-bit MF-RALU includes arithmetic, logical, complement, shifters, multiplexers, different adders, and multipliers. The multi-bit reversible multiplexers are used to construct the MF-RALU structure. The Reduced instruction set computer (RISC) processor is designed to realize the functionality of the MF-RALU. The MF-RALU can perform its operation in a single clock cycle. The 1-bit RALU is developed and compared with existing approaches with improvements in performance metrics. The 32-bit reversible arithmetic units (RAUs) and reversible logical units (RLUs) are constructed using 1-bit RALU. The MF-RALU and RISC processor are synthesized individually in the Vivado environment using Verilog-HDL and implemented on Artix-7 field programmable gate array (FPGA). The MF-RALU utilizes a <11% chip area and consumes 332 mW total power. The RISC processor utilizes a <3% chip area and works at 483 MHZ frequency by consuming 159 mW of total power on Artix-7 FPGA.